(3GdUGOM hGdHGZes - (3eMeO Hf eMeO Hf UGdM GdYHGSj, fXGe GdOjf CHh jYdj, GHf GdgHGQjI , J (B509 (3g` s
(3ChdgG (B:s
(3Chdg eHJhQ , hChd GdehLhO efg (B: (3aHJ ai CUd cfGS ai GdNeQ hbO ScQJ HGddZhH hGdSeQ aefeJ ddMjf LejY jhei Ke EfJHgJ aQbG ef fhei s
(3BNQgG (B:s
(3BNQg eHJhQ , hBNQ GdehLhO efg (B: (3Ef GdfahS GdaGFbI ddecQeGJ YGTbI bGdJ dgG GdNWHGA CMSfJ jG MSfGA s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH(B5s
(3HgG fXGe GdJYbjHIs
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd , eHJhQI GdBNQ s
(3GdfSNI HgG JdhjK , CQVg s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdTjN CMeO Hf eMeO GdSGdei GdNGUg s
Keywords: (3GdCOHs